Hubungan antara iklim sekolah dengan perilaku menyontek (academic cheating) pada siswa SMA di Malang - Mia Rista Ayustina; Nawang Warsi Wulandari; Deasy Christia Sera (University of Merdeka Malang, 2020)
Cheating is illegal, dishonest and cheating in getting answer during test or doing assignment. Cheating is a problem and a long standing phenomenon in the world of education. An unfavorable scholl climate is one of the causes of a decline in academic integrity. The purpose of the study was to determine the relationship between scholl climate and academic cheating behavior in high scholl students in Malang. This research is a quantitative study with research subjects 83 students of SMA Panjura Malang. Using a proportionate stratified random sampling technique with a scale of cheating behavior and school climate scale. The results showed that there was a relationship between school climate and student cheating behavior, where the more positive the school climate the students get, the lower the cheating behavior. Conversely, the lower the school climate the students get, the higher the cheating behavior of students in school. Based on the results of calculations show, the correlation index is -0.415 with a sign value. 0.000 (p 0.05).